State Policies for Undocumented Immigrants : Policy-Making and Outcomes in the U.S., 1998-2005. - Thangasamy, Andrew (New Americans (LFB Scholarly Publishing LLC), 2010)
Thangasamy examines state level policy making for undocumented immigrants in the United States between 1998 and 2005. This period saw heightened state legislative activity regarding access to higher education and the availability of driver?s licenses and health benefits for undocumented immigrants. Some states chose to extend these benefits to undocumented immigrants while some did not. Thangasamy seeks to explain the variation in state responses. He tested partisanship, interest group politics, bureaucratic politics, and the role of race and ethnicity to explain policy variation. While, neith.